Effect of zinc therapy in remission of pediatric nephrotic syndrome - Kumar, Dinesh; Arya, Priyanka; Sharma, Indra Kumar; Singh, Mukesh Vir (International Journal of Contemporary Pediatrics, 2017)
Background: Zinc has been used in diarrhea since long but their efficacy in nephrotic syndrome still requires evidences. The objectives of this study were to determine the effect of Zinc in nephrotic syndrome among the children in rural population. Methods: Randomized control trial. We included 60 children of age group 6 months - 15 years diagnosed as nephrotic syndrome and fulfilling the inclusion criteria. All children were given standard steroid therapy for duration depending on initial or relapse cases while intervention arm (n=30) were given zinc syrup at the dose 10 mg for less than 1 year and 20 mg for more than 1 year for 14 days apart from standard steroid therapy. Duration of remission in both the groups was measured as primary outcome while secondary outcome was duration of hospital stay in both control and study group. Results: Mean number of days taken in remission in study group was 11.8±3.96 days and in control group 18.3±5.14 days (p <0.001). Total duration of study in hospital in study group was 13.07±4.86 days and in control group was 20.50±7.06 days (p <0.001). Conclusions: Zinc significantly reduced the duration of hospital stay and remission in children suffering from nephrotic syndrome.